Vom Film als Verführer zum Film als Lehrer: Entwicklungslinien in der katholischen Filmarbeit - Hasenberg, Peter (Communicatio socialis, 2019)
The following article outlines lines of development of Catholic film work. The Catholic Church, originally depicted in film as an ethical problem, as a seducer with immoral purposes, attempted over the course of history to control the potentially damaging effect of the film medium. This was undertaken by establishing its own facilities in the fields of production, rental and projection, through statements and appeals and, in particular, through journalistic activities, which aimed to control the behavior of the public. During the course of these developments, the aim of the church to control as well as the overall potential of film to influence the public disappeared. To provide impulses towards reflection on questions related to meaning and value, were increasingly and more clearly recognized as important.